Measuring Cues of Leadership, Cohesion, and Fluidity in Joint Full-Body Movement to Support Embodied Interaction Design: A Pilot Study - Giorgio Gnecco; Antonio Camurri; Cora Gasparotti; Eleonora Ceccaldi; Gualtiero Volpe; Benoît Bardy; Marta Bieńkiewicz; Stefan Janaqi (Human Behavior and Emerging Technologies)
Innovative applications of human movement analysis, for example, for mitigating/slowing down certain pathological conditions, have recently emerged from the modeling and automated measurement of full-body expressive midlevel individual and group movement qualities, at a higher complexity level than movement qualities derived directly from physical signals, still not characterizing any gesture in a specific way. More in general, the availability of automated analysis techniques of midlevel expressive movement qualities can contribute to interaction design incorporating body-based performance practices inspired by artistic theories in dance and music. This work investigates how such practices and techniques can support embodied interaction design by enabling automated measuring of cues of leadership, cohesion, and fluidity in full-body movement in group settings. In particular, the dance-inspired scientific approach, the data collection protocol, and the analysis techniques adopted for assessing movement qualities connected to leadership and cohesion within the group and fluidity of the dancers’ full-body movement are described. Finally, future developments of this research are outlined.